Teaching Islam in Israeli Institutions of Higher Education - Daniella Talmon-Heller (International Institute of Islamic Thought, 2007)
The idea of a workshop dedicated to the teaching of Islam was conceived by Israeli academics who teach “Introduction to Islam.” This course is obligatory in all Islamic and Middle Eastern studies departments in Israeli universities and colleges, and is a popular elective course for students from various faculties. Indeed, it is a demanding mission. While teaching Islam or, for that matter, any religious tradition to those who are new to the scholarly critical approach to religion may be challenging anywhere,1 the Israeli setting poses additional difficulties. It involves teaching in classes composed of a mixed crowd of Jewish, Muslim, and Christian students, some of whom are deeply committed to their faith, while others are quite secular. The tense climate of the Arab-Israeli conflict inevitably shapes, in one way or other, the learning environment. The uneven power relations inside Israel, often unacknowledged yet very present, as well as the prevalent stereotypes and prejudices about Islam in Israeli society and media also impact the classes and teachers. All that aside, many of the teachers who deliver this introductory course shared an urgent need to rethink and revise the “classical” syllabus, one formulated by the great founders of Islamic studies in Israel decades ago. To this end, a good number of full professors, associate professors, young instructors, and some graduate students from all of Israel’s five universities, as well as from its colleges and seminaries for high-school teachers, got together for an intensive day of exchanging ideas ...